P162 How many and how much? Assessing resource utilisation in Multi-drug Resistant Tuberculosis (MDR TB) management using routinely collected hospital data. (16th November 2010) - José, R J; Smith, C; Breen, R; Marshall, N; Cropley, I; Hopkins, S; Lipman, M C I
Abstract : Introduction: MDR TB is rare in the UK, yet its incidence is rising. Although treatment is intensive, prolonged and generally costly for the patient and the treating TB centre, more TB services are offering such care. In the last 10 years, despite considerable relevant health service reorganisation, there has been no UK-based assessment of its resource implications, or guidance on how to determine this. Here we explore how routinely collected hospital data may assist in mapping service utilisation and also provide possible quality indicators of care. Methods: We performed a retrospective case-control study using MDR TB patients starting treatment between 2004 and 2007. Cases were matched to drug sensitive TB controls (1:2) treated in the same regional centre using age, sex, site of disease, HIV status and year of diagnosis. Data were abstracted from hospital clinical systems and matched analysis of service utilisation was performed. Results: 9 patients (8 pulmonary and 1 spinal) were included in the MDR TB and 17 (16 pulmonary and 1 spinal) in the control group. All patients completed treatment successfully. The Abstract P162 Table 1 indicates that MDR TB patients used a larger number of anti-tuberculosis drugs for longer, attended outpatients more frequently and made considerably greater use of biochemical, haematological and simple radiological assessments. However, there was no significant difference in total inpatient length of stay. All MDR TB patients reported adverse events requiring a change to medication or additional therapy to control these effects—this compared to 33% of controls (p<0.05). Drug-induced hepatitis was no more frequent (22% vs 18%, MDR vs controls, p=0.75). Some patient safety investigations, such as antibiotic drug levels and audiometry, were only performed in MDR TB patients. Conclusion: MDR TB remains a highly resource-intensive area of TB care. Modern NHS data systems are capable of recording utilisation and timing of specialist tests. These simple measures can allow services to develop patient-focussed quality outcomes as well as feedback results to clinicians to improve cost-effectiveness in specialist MDR TB management.